Social transformation and cohabitation culture - Chamseddine Habib Allah, Mohamed (International Journal of New Education, 2019)
Growing presence of migrants from multiple places in Spain is of a very significant quantitative importance regarding the population pyramid. This dynamic and changing reality poses new challenges in transformation and social cohesion in a complex scenario, with numerous open fronts to manage. This work main objective focuses on exploring cohabitation state in contexts with high and low cultural diversity, describing at the same time the interactions in different spaces and shared resources in Región de Murcia. The results indicate that intercultural interactions are expressed differently, depending on the context and the cultural diversity degree of each community. In the light of these findings, it is considered necessary to manage coexistence by investing passive respect and indifference in peaceful and positive interactions aimed at building a cohabitation culture.